Assessment of Spatial Variability of Soil Available Sulphur Using Geostatistical Techniques in a Part of Deccan Plateau of India - Rabi Narayan Sahoo (Journal of the Indian Society of Soil Science, 2022)
Soil heterogeneity, soil formation factors and other human induced activities cause spatial variation of soilavailable nutrients. Knowledge on spatial variability of soil nutrients is essential for their successfulmanagement in crop field. Soil available sulphur (S) is an important secondary nutrient and it may varyspatially at any scale. Hence, the present study was conducted to assess the spatial variability of soilavailable S using geostatistical techniques. About 132 georeferenced surface soil samples were collectedform a cultivated area of Katol block of Nagpur district, Maharashtra, India. Soil available S was determinedchemically and the descriptive statistical analysis of S showed its good variability in terms of per centcoefficient of variation (CV= 81.74%). The results of geostatistical analysis showed its spatial variability interms of nugget: sill ratio (NS ratio). The NS ratio i.e., 0.37 indicated moderate spatial dependency of soilavailable S. The exponential model was found as a best suited semivariogram model for describing thespatial trend of soil S. Ordinary kriging (OK) technique was employed to generate spatial variability map ofsoil S to identify specific management zone of S. The present investigation suggested that the study areahas moderate S content except north-east corner of the area, which is high in S content. Specific managementof S is necessary to the central and north-west sides of the cropped areas of the study site. Thus, the studyindicated a good potential of geostatistical technique especially with OK technique to generate S variabilitymap for effective S management of the study area.